(untitled) (Scientific journal of the Fergana State University, 2024)
Currently, in the development of interesting methodologies for determining the effectiveness indicators and levels of the biological sciences education system, in order to reveal its validity in the process of evaluating the knowledge of students, to carry out continuous control of the quality of education and the training of real personnel of the biology department various researches are being conducted to increase the level. From this point of view, the problem of "improving the processes of monitoring and evaluating the quality of education and its tools, putting into practice the tools that can determine the level of the obtained results", improving the functional literacy of students in biology classes, and adapting their knowledge assessment to international assessment standards determines the relevance of our scientific work. The analysis of the results of the international comparison in the educational system shows that the students of the educational institutions of the school education have a very strong knowledge of subjects within the scope of biology or natural sciences. Examples of the so-called functional literacy were developed in the process of bringing the acquired knowledge to the level of skill and competence. It develops the ability of students to find and implement the best ways to solve problems that arise in the course of life, along with putting knowledge into practice, applying it, and strengthening biological knowledge. It is revealed the importance of strengthening the methodical support for the formation of students’ functional literacy in the digital educational environment in accordance with the modern development and the search for factors that help to increase its effectiveness.